Antioxidant Compounds from The Stem Bark of Syzygium samarangense L - Seni Metasari; Elfita Elfita; Muharni Muharni; Heni Yohandini (Universitas Jenderal Soedirman, 2020)
Ogan ethnic community in South Sumatera has been used a decoction of the stem bark of Syzygium samarangense L (locally named “jambu air” in Indonesia) for hypertension medicine. Hypertension is a degenerative disease caused by free radical activity in the body. This study aims to scientifically prove the use of a decoction of the stem bark of S. samarangense so that its use by the Ogan ethnic community can be justified. The research began with fractionation of the stem bark by gradient solvents, and each fraction was tested for antioxidant activity. Isolation of antioxidant compounds from active fractions was carried out by chromatographic techniques. Antioxidant tests on fractions and pure compounds were carried out by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Based on spectroscopic data analysis and by comparing with literature, the pure compounds were identified as quercetin and gallic acid. Both of these compounds have strong antioxidant activity with IC50 quercetin 11.16 and gallic acid 11.43 µg/mL. This research proves that the use of the stem bark of S. samarangense for a degenerative disease by the Ogan ethnic community contains the truth.